Carbide-metal assemblages in a sample returned from asteroid 25143 Itokawa: Evidence for methane-rich fluids during metamorphism. (1st February 2018) - Harries, Dennis; Langenhorst, Falko
Abstract: We found that the particle RA-QD02-0115 returned by the Hayabusa spacecraft from near-Earth asteroid 25143 Itokawa contains the iron carbide haxonite (Fe21.9-22.7 Co0.2-0.3 Ni0.2-0.8 )C6 and several Fe, Ni alloys, including multi-domain tetrataenite and spinodally decomposed taenite. Ellipsoidal to nearly spherical voids occur throughout the particle and suggest the presence of a fluid phase during textural and chemical equilibration of the host rock within the parent asteroid of 25143 Itokawa. The calculated solubility of carbon in Fe, Ni metal indicates that the carbide formed at temperatures larger than 600 °C during thermal metamorphism of the LL-chondritic mineral assemblage. Haxonite formed metastably with respect to graphite and cohenite, probably due to its high degree of lattice match with neighboring taenite, a low cooling rate at peak metamorphic temperatures, and the hindered nucleation of graphite. Thermodynamic equilibrium calculations indicate that the fluid present was dry (H2 O-poor) and dominated by methane. The reactive fluid most plausibly had an atomic H/C ratio of 4–5 and was derived from the reduction of macromolecular, insoluble organic matter (IOM) that initially co-accreted with water ice. The initial presence of water is a necessary assumption to provide sufficient hydrogen for the formation of methane from hydrolyzed IOM. Metallic iron was in turn partially oxidized and incorporated into the ferromagnesian silicates during the high-temperature stage of metamorphism. An exemplary bulk reaction from unequilibrated material on the left to an equilibrated assemblage on the right may be written as: 330 CH0.8 O0.2(IOM)  + 500 H2 O(ice/g)  + 681 Fe(in alloy)  + 566 FeSiO3(in Opx)  → 300 CH4(g)  + 32 H2(g)  + 5 Fe23 C6(in Hx)  + 566 Fe2 SiO4(in Ol) (Opx = orthopyroxene, Hx = haxonite, Ol = olivine, g = fluid species). The best estimate of the fluid/rock ratio in the region of the LL parent body where RA-QD02-0115 formed is about 3 × 10 −3 and corresponds to an initial ice/rock ratio of about 7 × 10 −3 (both by mass).